Evidence from Site-directed Mutagenesis that the Cytoplasmic Domain of the β3 Subunit Influences the Conformational State of the αvβ3 Integrin Ectodomain - Schaffner-Reckinger, Elisabeth; Brons, Nicolaas H. C.; Kieffer, Nelly (Thrombosis and Haemostasis, 2001)
In order to explore the mechanisms leading to conformational changes of the vitronectin receptor αvβ3 following ligand or divalent cation binding, we have investigated the expression of epitopes known as ligand-induced binding sites (LIBS) on 3 cytoplasmic tail mutants expressed in CHO cells. Truncation of the entire 3 cytoplasmic domain induced constitutive LIBS exposure on αvβ3 and IIb β3. Deletion of the C-terminal NITY759 sequence or disruption of the NPLY747 motif by a Y747A substitution impaired extracellular conformational changes on αvβ3 following RGDS, echistatin or Mn2+ binding, whereas the substitutions Y747F, Y759A or Y759F allowed normal LIBS exposure. Furthermore, metabolic energy depletion totally prevented Mn2+-dependent LIBS exposure, but had only a minor effect on RGDS-induced conformational changes. Our results demonstrate that the structural integrity of the NPLY747 motif in the β3 cytoplasmic domain, rather than potential phosphorylation of Tyr747 or Tyr759, is a prerequisite for conformational changes within the αvβ3 ectodo-main, and suggest that two different mechanisms are responsible for RGDS- and Mn2+-dependent conformational changes.
Keywords: Integrin αvβ3; LIBS epitope; cytoplasmic domain; conformation; metabolic energy